Voices in the History of Madness Personal and Professional Perspectives on Mental Health and Illness - Robert Ellis (Mental Health in Historical Perspective (MHHP), 2021)
This interdisciplinary volume brings together new research that broadens our understanding of the multiplicity of voices in the histories of mental ill-health. In the chapters that follow, we hear from people who have experienced mental health difficulties and were on the receiving end of regimens and treatments. Alongside medical notes, we find records of decisions made by a range of people with financial and political agendas. Correspondence with families reminds us that people deemed to be mentally ill were not ciphers; they had their histories, their people, preferences, hopes and losses. The contributions utilise a range of archival materials, oral history, personal testimony, history of art, and literary methodologies and provide novel insights into the voices of individuals, institutions, and communities in an international context. Key overlapping themes divide the volume into four parts: Shifting Perspectives in the Industry of Madness; Reconstructing Patient Perspectives; The Visual and the Material; and Mad Studies and Activism